Методика оцінки фінансового потенціалу розвитку підприємства та напрямки її вдосконалення - Стародуб, Вікторія Вікторівна; Starodub, Viktoriya Viktorivna (Ірпінь, 2024)
Структурно робота складається із трьох логічно сформованих розділів. У першому розділі розкрито наукові підходи до визначення сутності фінансового потенціалу підприємства; розглянуто методичні підходи до оцінки фінансового потенціалу розвитку підприємства. У другому розділі проведено аналіз стану та основні тенденції розвитку господарської діяльності ПрАТ «Київський меблевий комбінат»; зроблено оцінку ефективності використання фінансового потенціалу ПрАТ «Київський меблевий комбінат». Третій розділ присвячено напрямам вдосконалення оцінки фінансового потенціалу ПрАТ «Київський меблевий комбінат».

Structurally, the work consists of three logically formed sections. The first chapter reveals scientific approaches to determining the essence of the financial potential of the enterprise; methodical approaches to assessing the financial potential of enterprise development are considered. In the second section, an analysis of the state and main trends in the development of the economic activity of PJSC "Kyiv Furniture Factory" was carried out; an assessment of the effectiveness of using the financial potential of PJSC "Kyiv Furniture Factory" was made. The third section is devoted to directions for improving the assessment of the financial potential of Kyiv Furniture Combine PJSC.
Methodology for assessing the financial potential of enterprise development and directions for its improvement
Keywords: фінансовий потенціал; методика; оцінка; фінансовий стан; financial potential; methodology; evaluation; financial status